Use of educational design in the design of the Computer Programming teaching project in the Distance Education mode (Research, Society and Development, 2017)
The objective of this article is to present the conception of a computer programming teaching project in Distance Education (EAD) for a group of students from a vocational course in the city of Novo Hamburgo (RS). The target audience is 25 young people with an average age of 20, who are preparing to work in the area of Information Technology as programmers. After a basic training of a semester, are introduced to the study of structured programming languages of computers, in this specific case the programming language C. After the face-to-face training, the students have a discipline in the EAD mode. This project is composed as Individual classes of two and a half hours, totaling 8 lessons and 24 hours total. Methodologically, this study presents a qualitative approach, using the case study category to analyze the question of learning in environments. The objective of this study is to demonstrate how educational design strategies can be used in practice to structure the Computer Programming discipline project in order to enhance learning in the EAD mode. The construction of this learning will be supported by the use of digital communication resources of Web 2.0, allowing the construction of the personal learning network (PLE) of the apprentices in an interactionist and collaborative perspective. It is hoped that the application of educational design methodologies and strategies, combined with Web 2.0 resources and PLE, will help young people to acquire the desired skills, preparing them to qualify their insertion in the job market.